Inside the Municipal Lobby: Explaining Local Government Influence on the New EU Public Procurement Directives (Lex localis - Journal of Local Self-Government, 2018)
Despite a challenging context, local authorities succeeded in influencing one of the most fiercely debated issues of the new EU Public Procurement Directives (2014): the (conditional) exemption of public-public cooperation (PPC). Using theory-building process-tracing this paper analyses the PPC-case to design a parsimonious causal model of successful municipal lobbying under challenging circumstances. The model represents a composed mechanism that triggered municipal lobby influence through the interplay of three basic parts: a strategic lobby campaign deployed by a strong protagonist, an external opportunity structure underpinning and strengthening the latter and a significantly receptive EU decision-making arena. Furthermore, the case suggests that in challenging lobby cases local government can profit from its distinctive character as an electorally legitimised and politically connected interest group to promote its interests in the EU polity.